Effects of acute and long-term mindfulness on neural activity and the conflict resolution component of attention - Elcin, Dehan; Velasquez, Miguel; Colombo, Paul J. (Frontiers in Human Neuroscience, 2024)
Mindfulness practices have been linked to enhanced attention and conflict resolution abilities. While much research has focused on the long-term effects of mindfulness, the immediate impact of a single session has been less studied. This study recruited 20 experienced meditators and 20 novices and assigned them to a mindfulness or a control condition. They completed a Stroop Task to measure cognitive conflict resolution before and after the intervention, with brain activity monitored via functional near-infrared spectroscopy (fNIRS). Novices showed an age-related decline in conflict resolution ability, while experienced meditators didn't. Initially, both groups showed similar Stroop performance, but experienced meditators had greater brain activation in the left dorsolateral prefrontal cortex (DLPFC). Post-intervention, novices in the breath count task became more similar to experienced meditators in their neural activity during conflict resolution. Our findings indicate that long-term mindfulness experience may protect against age-related decline in cognitive conflict resolution speed, and may alter neural processing of cognitive conflict resolution.